Risk Management 4.0: The Role of Big Data Analytics in the Bank Sector - Dicuonzo, Grazia; Galeone, Graziana; Zappimbulso, Erika; Dell’Atti, Vittorio (International Journal of Economics and Financial Issues, 2019)
The need to query large volumes of heterogeneous data in differing formats from multiple sources, both internal and external and its centrality to the process of value creation is revolutionising traditional approaches to business models. Through the adoption of more sophisticated algorithms, it is possible to intercept and interpret any digital flow, particularly those coming from the Internet of Things or from the web. The vast amount of information, its governance and its global integration are used in all decision-making processes and they are, therefore, an element of strategic importance in the development process and in the survival of every company, thanks to the potential for transforming all information sources into knowledge and quantifying reality in all its elements (objects, places, phenomena, people and human behaviour). Having a large volume and a wide variety of information (i.e. Big Data) shared within an organisation is crucial for the interactive and multidirectional process of risk assessment and management. This process, on the one hand, contributes to safeguarding the integrity of corporate assets through increased efficiency and the effectiveness of the services provided and, on the other, reduces unexpected events and related losses while ensuring greater efficiency in the decision-making process. This is relevant especially in financial institutions in which risk management is pivotal to their survival and their success, assuming a strategic role. Through an analysis of the literature and a case study methodology, this paper investigates how small banks are facing technological challenges, showing the state of art about the actual use of the techniques of data collection and management (e.g. Big Data analytics) in supporting the risk management process. Furthermore, the work tries to identify the skills required of the risk manager in the digital age. The paper contributes to the ongoing debate on the usefulness and use of digital innovations in the banking sector, discussing the future perspectives of risk management 4.0 and the role of Big Data analytics in risk management. Keywords: Big Data Analytics, Business Intelligence, Risk Management, Decision Making, Case study, Banks JEL Classifications: O3, G2, M1 DOI: https://doi.org/10.32479/ijefi.8556